The Antibacterial and Antibiofilm Efficacy of Citrullus lanatus Rind Ethanol Extract Against Aggregatibacter actinomycetemcomitans - Cokro, Wilbert Alvin Genesis; Natassya, Priska; Soesanto, Sheila (Biology, Medicine, & Natural Product Chemistry, 2024)
Watermelon (Citrullus lanatus) rind contains secondary metabolite compounds which exhibit antimicrobial effects against Gram-positive and Gram-negative bacteria. Aggregatibacter actinomycetemcomitans can cause tissue damage and bone resorption, leading to aggressive periodontitis. Chlorhexidine as golden standard antimicrobial mouthwash can cause tooth staining. There is a need for herbal remedies with fewer side effects as an alternative treatment for periodontitis. This study aims to determine the antibacterial and antibiofilm efficacy of C. lanatus rind ethanol extract against A. actinomycetemcomitans. This is an experimental laboratory in vitro with a post-test-only control group design. The antibacterial test was conducted using the plate count method and the antibiofilm test using the microtiter plate biofilm assay method. The samples used were ethanol extract of C. lanatus rind 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%, chlorhexidine 0.2% as positive control, distilled water, and BHI-B as negative control. As a result, extract concentrations from 12.5% to 100% exhibited antibacterial effects on A. actinomycetemcomitans equivalent to chlorhexidine. During the 3-hour incubation period, extract at 25% and 100% concentrations on all incubation times showed a better antibiofilm effect than chlorhexidine. It can be concluded that ethanol extract of C. lanatus rind had the potential as an alternative antibiofilm agent against A. actinomycetemcomitans.